Pengaruh Strategi Pemasaran Berbasis Flash Sale, Promosi Penjualan, Online Customer Review Dan Gratis Ongkos Kirim Terhadap Minat Beli Di E-Commerce Tiktok Shop (Studi Kasus Pada Generasi Z Kecamatan Lowokwaru Kota Malang) - Siba, Fadila Hasna; Asiyah, Siti; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study was to determine how the simulthaneous and partial influence of Flash Sale, Sales Promotion, Online Customer Review, and Free Shipping on purchase interest in Tiktok Shop E-commerce on Generation Z in Lowokwaru District, Malang City. The type of research used in this study is Quantitative with the Explonatory Reseacrh approach method. The type of population to be studied is unlimited, because the researcher does not know the exact number of Generation Z consumers who make purchases on Tikrom Shop E-commerce. Sampling was carried out using the purposive sampling method using the Maholtra formula 22 x 5 = 110 respondents. Data collection in this study throught questionnaires distributed to all Generation Z in Lowokwaru District, Malang City which is the location of this study. The analysis tool uses SPSS 26. Flash Sale, Sales Promotion, Online Customer Review, and Free Shipping have a simultaneous effect on Purchase Interest. Flash Sale has a significant effect on Purchase Interest, Sales Promotion has a significant effect on Purchase Interest, Online Customer Review has a significant effect on Purchase Interest, Free Shipping has a significant effect on Purchase Interest. Keywords: Flash Sale, Sales Promotion, Online Customer Review, and Free Shipping.